The linguistic research approach of Al-Farabi (339 AH) In his book (The Letters) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the master of the messengers and his family and companions. As for after..This is Al-Farabi Abu Nasr Muhammad bin Muhammad, the philosopher, the second teacher, the author of philosophical theories and logical arguments, and these titles we used when he mentioned Al-Farabi, but the linguistic side did not take as much attention as the philosophical side, so the longing prompted me to study his linguistic approach, and my studies focused on researching The linguistic side, after I searched the title (letters) and its relationship to the content, which I found that the title did not cover the content. And Praise be to Allah, the Lord of the Worlds.